Lelampaq Lendong Kaoq: Comic Design to Strengthen Local Literacy - Hasbullah, Hasbullah; Lukman, Lukman; I Nyoman Yoga Sumadewa; Sasih Gunalan (Meraki: Journal of Creative Industries, 2025)
A high level of reading literacy is very important for the nation's progress, however the reading literacy of students in Indonesia is still below the international average. To overcome this, the government instructed every school, including junior high schools, to allocate special time for literacy activities. One effective way is to provide interesting reading books, such as comics, which students prefer. At Mataram City Middle School, students tend to be less familiar with local folklore, so it is necessary to introduce stories such as "Lelampaq Lendong Kao," which contains a good moral message. Therefore, the designer plans to make the comic "Lelampaq Lendong Kao" using the design thinking method to design the right work. Apart from comics, supporting media such as t-shirts, posters and mugs will also be created to support the attraction. With this design, it is hoped that students will be more interested in reading, both during literacy hours and in their free time.